Remifentanil-ketamine vs. propofol-ketamine for sedation in pediatric patients undergoing colonoscopy: A randomized clinical trial - Karacaer,Feride (2018)
Abstract Background and objectives: Pediatric patients frequently require deep sedation or general anesthesia for colonoscopy. This study was designed to compare the sedative efficacy of remifentanil-ketamine combination with propofol-ketamine combination in children undergoing colonoscopy. Methods: Seventy patients, between 2 and 16 years of age, scheduled for diagnostic colonoscopy were randomly allocated into two groups. Remifentanil-ketamine group received intravenous ketamine 2 mg.kg−1 and remifentanil 0.25 µg.kg−1 combination, followed by 0.1 µg.kg−1.min−1 remifentanil infusion. Propofol-ketamine group received intravenous propofol 1 and 2 mg.kg−1 ketamine combination, followed by 1 mg.kg−1.h−1 propofol infusion. In the case of children discomfort (cry, movement, and cough), remifentanil 0.1 µg.kg−1 in the remifentanil-ketamine group or propofol 0.5 mg.kg−1 in the propofol-ketamine group were administered to improve children discomfort. Despite the therapy given above, if children still experience discomfort, 1 mg.kg−1 of ketamine was administered as a rescue drug, regardless of the group. Ramsay sedation score, hemodynamic variables, drug requirements, gastroenterologists' satisfaction, colonoscopy duration, recovery time, and side effects were recorded throughout the procedure and the recovery period. Results: The percentage of patients with a Ramsay sedation score of 4 or higher during the procedure was 73.5 and 37.1% in remifentanil-ketamine and propofol-ketamine groups, respectively (p = 0.02). Systolic and diastolic blood pressure variables were significantly higher only after induction in the remifentanil-ketamine group than in the propofol-ketamine group (p = 0.015). Conclusion: Coadministration of ketamine with either remifentanil or propofol effectively and safely provides sedation and analgesia in children undergoing colonoscopy. Sedation scores were significantly better in remifentanil-ketamine group than in propofol-ketamine group.